Thermally stratified radiative flow of non-Newtonian fluid between two discs executing diverse type of in-plane motion - Muhammad Asif Jafar; Zaheer Abbas; Jafar Hasnain (Case Studies in Thermal Engineering, 2021)
The study on heat transfer for non-Newtonian (Casson) fluid motion affected by thermal stratification and thermal radiation is carried out in the presence of vertically applied magnetic field normal to the discs. The uniqueness of the problem is that the flow is in between parallel discs which execute the diverse type of in-plane motion. The fluid flow is driven by the upper disc radially stretching/shrinking at the a rate and the lower disc rotating at the angular velocity Ω and h is the space between the discs. Using appropriate reduction parameters, the Navier-Stokes equations and heat equation are simplified to non-dimensional coupled ordinary differential equations. The impacts of the rotation parameter, Casson parameter, thermal stratification parameter, thermal radiation parameter and Reynolds number are discussed. The results obtained asymptotically and numerically. For the results' compatibility, the comparison is made with the previous study.